Treatment with Mycobacterium vaccae ameliorates airway histopathology in a murine model of asthma - AKKOÇ, TUNÇ (OCEAN SIDE PUBLICATIONS INC, 2008)
The objective of this study was to evaluate the effect of intratracheal (i.t.) or subcutaneous (s.c.) Mycobacterium vaccae treatment on lung histopathology and cytokine responses in a murine model of asthma. BALB/c mice were divided into four groups. To establish an asthma model, Groups I, II and III received intraperitoneal (i.p.) ovalbumin (OVA) and were challenged with i.t. OVA three times (days 41-47). On the same days, mice in Groups I and II were treated with i.t. and s.c. Mycobacterium vaccae, respectively. Mice in Group IV served as controls. On day 49, lungs were taken out for histopathological evaluation. Cytokine levels were determined in splenocyte culture supernatants by ELISA. The thickness of basement membrane and hyperplasic goblet cells in small airways were found to be significantly more in Group III than Group I. Furthermore, smooth muscle and epithelial thickness in small and large airways and hyperplasic goblet cell numbers in all sized airways of this treatment group were not significantly different from controls. Epithelial thickness in medium and large airways, hyperplasic goblet cells in all sized airways, and basement membrane in small and large airways were not significantly different in Group II when compared to controls. OVA-stimulated IL-5 levels was significantly higher in Group I when compared to Group III. OVA-stimulated IL-5 and spontaneous IL-5 levels were significantly higher in Group 11 than Group III. We demonstrate that subcutaneous and intratracheal Mycobacterium vaccae administered along with allergen has an ameliorating effect in the modulation of airway histopathological changes in OVA sensitized mice.
Keywords: airway histopathology; asthma; Balb/c mice; interleukin-10; interleukin-5; Mycobacterium vaccae; OVA sensitization; SENSITIZATION; INFECTION; OVALBUMIN; BOVIS; MICE